Norepinephrine transporter heterozygous knockout mice exhibit altered transport and behavior. (9th October 2013) - Fentress, H. M.; Klar, R.; Krueger, J. J.; Sabb, T.; Redmon, S. N.; Wallace, N. M.; Shirey‐Rice, J. K.; Hahn, M. K.
Abstract : The norepinephrine (NE) transporter (NET) regulates synaptic NE availability for noradrenergic signaling in the brain and sympathetic nervous system. Although genetic variation leading to a loss of NET expression has been implicated in psychiatric and cardiovascular disorders, complete NET deficiency has not been found in people, limiting the utility of NET knockout mice as a model for genetically driven NET dysfunction. Here, we investigate NET expression in NET heterozygous knockout male mice (NET +/− ), demonstrating that they display an approximately 50% reduction in NET protein levels. Surprisingly, these mice display no significant deficit in NET activity assessed in hippocampal and cortical synaptosomes. We found that this compensation in NET activity was due to enhanced activity of surface‐resident transporters, as opposed to surface recruitment of NET protein or compensation through other transport mechanisms, including serotonin, dopamine or organic cation transporters. We hypothesize that loss of NET protein in the NET +/− mouse establishes an activated state of existing surface NET proteins. The NET +/− mice exhibit increased anxiety in the open field and light–dark box and display deficits in reversal learning in the Morris water maze. These data suggest that recovery of near basal activity in NET +/− mice appears to be insufficient to limit anxiety responses or support cognitive performance that might involve noradrenergic neurotransmission. The NET +/− mice represent a unique model to study the loss and resultant compensatory changes in NET that may be relevant to behavior and physiology in human NET deficiency disorders . Abstract : The NET +/− mice compensate for a deficit in NET plasma membrane expression with normal NE transport activity.